2002
DOI: 10.1051/0004-6361:20011488
|View full text |Cite
|
Sign up to set email alerts
|

Using Cepheids to determine the galactic abundance gradient

Abstract: Abstract.A number of studies of abundance gradients in the galactic disk have been performed in recent years. The results obtained are rather disparate: from no detectable gradient to a rather significant slope of about −0.1 dex kpc −1 . The present study concerns the abundance gradient based on the spectroscopic analysis of a sample of classical Cepheids. These stars enable one to obtain reliable abundances of a variety of chemical elements. Additionally, they have well determined distances which allow an acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
138
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 62 publications
(39 reference statements)
25
138
2
Order By: Relevance
“…Data on cepheid variables should in principle agree with the B star results, which is confirmed by a recent analysis by Caputo et al (2001), but a flatter gradient and/or a discontinuity around 10 kpc is suggested from the high resolution data by Andrievsky et al (2002).…”
Section: Abundance Gradients From Pnsupporting
confidence: 80%
“…Data on cepheid variables should in principle agree with the B star results, which is confirmed by a recent analysis by Caputo et al (2001), but a flatter gradient and/or a discontinuity around 10 kpc is suggested from the high resolution data by Andrievsky et al (2002).…”
Section: Abundance Gradients From Pnsupporting
confidence: 80%
“…3 include the recent cepheid results from Andrievsky et al (2002), shown as open circles, and H II regions from the optical emission lines analyzed by Deharveng et al (2000), shown as six-pointed stars, and H II region far-IR fine-structure lines by Simpson et al (1995) and Afflerbach et al (1997), shown as three-pointed stars.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the value of the oxygen abundance at the solar galactocentric distance (12+logO/H∼8.6) derived by Andrievsky et al (2002) from the study of Cepheids and the value of the oxygen abundance (12+logO/H∼8.5) derived by Daflon et al (1999Daflon et al ( , 2001) from the study of OB stars are in agreement with the oxygen abundance in the solar vicinity region derived from the interstellar absorption towards stars and from the study of H ii regions. At the same time, there is an appreciable disagreement between values of the radial oxygen abundance gradient derived from the study of Cepheids (-0.022dex/kpc, Andrievsky et al 2002), from the study of early Btype main-sequence stars (-0.067dex/kpc, Rolleston et al 2000), and from the study of H ii regions (-0.048dex/kpc, this study).…”
Section: The Oxygen Abundance In the Solar Vicinitysupporting
confidence: 83%
“…At the same time, there is an appreciable disagreement between values of the radial oxygen abundance gradient derived from the study of Cepheids (-0.022dex/kpc, Andrievsky et al 2002), from the study of early Btype main-sequence stars (-0.067dex/kpc, Rolleston et al 2000), and from the study of H ii regions (-0.048dex/kpc, this study). This disagreement can be explained by two reasons.…”
Section: The Oxygen Abundance In the Solar Vicinitymentioning
confidence: 56%
See 1 more Smart Citation